Expanding the boundaries of metal deposition: High aspect ratio silver nanoplatelets created by merging nanobelts. (20th February 2018) - Muench, Falk; Vaskevich, Alexander; Popovitz-Biro, Ronit; Bendikov, Tatyana; Feldman, Yishay; Rubinstein, Israel
Abstract: Metal nanoplatelets (NPLs) display an important class of nanomaterials, whose morphological diversity is limited due to the uniform mechanisms governing their growth. Here, we introduce a new electroless plating (EP) strategy based on a metal complex surfactant, which is capable of producing a variety of previously undescribed silver NPL architectures. Our NPL formation can be understood as a unique example of space-filling dendritic growth. Likewise to conventional colloidal syntheses, in-plane growth is promoted by stacking faults, while out-of-plane growth on 111 is efficiently suppressed. Remarkably, the passivation extends to the nanostructure edges, limiting in-plane growth to random, localized nucleation events, which constantly change direction within a privileged set of six <211> vectors. Out-of-plane growth proceeds discontinuously, by the formation of separate NPL layers with the same morphology. The nucleation probabilities change throughout the reaction, causing the deposit morphology to transition from individual nanobelts (NBs) over NPLs to porous dendrite-like sheets, under retention of the internal nanostructure. The synthesis is facile, scalable, tunable and applicable to various substrate materials, and thus represents a powerful tool for the direct modification of surfaces with anisotropic nanostructures. Graphical abstract: Highlights: Electroless plating of silver nanoplatelet films on various substrate materials. Shape selectivity induced by Fe(III) tartrate complex surfactant. Passivation of 111, anisotropic growth in <211> guided by stacking faults. Nanostructure evolution: 1D nanobelts > 2D nanoplatelets > 2D dendritic sheets. Morphological transformation caused by changing nucleation probability.